A 3‐year longitudinal survey of overactive bladder in community‐dwelling male residents aged 40 years and above. Issue 3 (17th February 2021) - Yang, Evelyn; Hu, Suh‐Woan; Chen, Sung‐Lang; Chen, Gin‐Den; Ng, Soo‐Cheen
Abstract: Objectives: To evaluate the short‐term evolution and risk factors of overactive bladder (OAB) in community‐dwelling male residents aged 40 years and above in central Taiwan. Methods: This was a 3‐year longitudinal cohort study. From January 2012 to December 2012, community residents aged 40 years and above, living in central Taiwan, were invited to participate in this study. A yearly Overactive Bladder Symptom Score (OABSS) questionnaire was used to assess the prevalence, incidence, remission, persistence, and relapse of OAB for three consecutive years. OAB was defined as total OABSS ≧4 and urgency score ≧2. Results: Nine hundred forty‐one male residents aged ≧40 years were recruited. The prevalence of OAB was 15%. The male residents with OAB were older, had a history of urological surgery, were unemployed, had lower educational levels, and lower yearly incomes compared with male residents without OAB. The prevalence increased with age when stratified into different age cohorts (40‐49, 7%; 50‐59, 12.7%; 60‐69, 18.2%; ≧70, 32%; P  < .001). Age ≧60 (odds ratio [OR] 2.58; 95% CI, 1.62‐4.11) and history of urological surgery (OR 2.85; 95% CI, 1.29‐6.30) were the major risk factors after multivariable logistic regression analysis. Eight hundred participants completed all the 3 years' questionnaires. The second‐ and third‐year incidence rates of OAB were 10% (69/691) and 6.2% (42/674), respectively. The remission rates were 47.7% (52/109) and 46% (58/126), respectively. The two‐year OAB persistence rate was 30.3% (33/109). Conclusions: The prevalence and yearly incidence of OAB are high in community‐dwelling male residents aged ≧40 years in central Taiwan. Age is an important risk factor.